1967
DOI: 10.1063/1.1841029
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Isotopic Disproportionation Reaction between Light and Heavy Water Using a Pulsed-Molecular-Beam Mass Spectrometer

Abstract: Isotopic exchange equilibrium in the disproportionation reaction H2O+D2O=2 HDO was studied at 0° and 25° and over a range of deuterium compositions using a pulsed-molecular-beam mass spectrometer. The equilibrium constant K was found to be 3.75±0.07 at both temperatures. The pulsed-beam mass spectrometer was shown to be effective in minimizing the ``memory effect'' in the mass spectrometer. The experimental K is shown to be consistent with equilibrium constants for similar isotopic disproportionation reactions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1973
1973
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…The two most recent liquid phase equilibrium constant measurements (at 298 K) are 3.86 Ϯ 0.07 [3] and 3.86 Ϯ 0.01 [27] [23] difference between liquid and gas-phase equilibrium constants is estimated to be only 0.03 [28]. Previous direct mass spectrometric measurements (carried out in the 1960s) have led to the values of K ϭ 3.75 Ϯ 0.07 [29] and 3.76 Ϯ 0.02 [26]; however, these measurements have been performed at electron accelerating voltages from 3 eV (H 2 O) [25] Se concentrations in the headspace. The resulting mixtures were then analyzed using GC/MS, and their composite mass spectra were decomposed using the weighted two band-target entropy minimization algorithm and the statistical model.…”
Section: Quantitation Of Isotopologues Using the Reconstructed Mass Smentioning
confidence: 91%
“…The two most recent liquid phase equilibrium constant measurements (at 298 K) are 3.86 Ϯ 0.07 [3] and 3.86 Ϯ 0.01 [27] [23] difference between liquid and gas-phase equilibrium constants is estimated to be only 0.03 [28]. Previous direct mass spectrometric measurements (carried out in the 1960s) have led to the values of K ϭ 3.75 Ϯ 0.07 [29] and 3.76 Ϯ 0.02 [26]; however, these measurements have been performed at electron accelerating voltages from 3 eV (H 2 O) [25] Se concentrations in the headspace. The resulting mixtures were then analyzed using GC/MS, and their composite mass spectra were decomposed using the weighted two band-target entropy minimization algorithm and the statistical model.…”
Section: Quantitation Of Isotopologues Using the Reconstructed Mass Smentioning
confidence: 91%
“…For the water vapor internal equilibrium reaction: H 2 O + D 2 O = 2HDO, large deviations were found between theoretical studies and experiments (Pyper et al, 1967;Pyper and Newbury, 1970;Pyper and Christensen, 1975). Wolfsberg (1969) showed that it was not sufficiently accurate to add anharmonic corrections without the contributions of G 0 terms to partition function ratios.…”
Section: Equilibrium Constant K With Corrections Beyond Harmonic Levelmentioning
confidence: 93%
“…[5] but disagree with those in Refs. [1][2][3][4], (See Table 1 The iteration computer code also calculated the sensitivity ratio, S., at seven different times. The ratios are shown in Table 5.…”
Section: Results and Discussion'mentioning
confidence: 99%
“…[1][2][3][4] and recent theoretical calculations[6-3j of K » 3.85 at 25*C might be the result of a value of S different from unity. The meastEreaetU of the sensitivities of isotoplc species of water Is complicated by the phenomenon known as taenory effect.…”
mentioning
confidence: 87%
See 1 more Smart Citation